Decreased Spinothalamic and Dorsal Column Medial Lemniscus-Mediated Function Is Associated with Neuropathic Pain after Spinal Cord Injury - Cruz-Almeida, Yenisel; Felix, Elizabeth R.; Martinez-Arizala, Alberto; Widerström-Noga, Eva G. (Journal of neurotrauma, 2012)
Neuropathic pain (NP) after spinal cord injury (SCI) can significantly and negatively affect quality of life and is often refractory to currently available treatments. In order to find more effective therapeutic avenues, it would be helpful to identify the primary underlying pathophysiological mechanisms in each individual. The aim of the present study was to assess the relationship between the presence and severity of NP after SCI and measures of somatosensory function mediated via the dorsal column medial lemniscal (DCML) pathway and the spinothalamic tract (STT). Vibratory, mechanical, thermal, and pain thresholds measured in areas at and below the neurological level of injury (LOI) in persons with SCI and NP (SCI-NP, n=47) and in persons with SCI without NP (SCI-noNP, n=18) were normalized to data obtained from able-bodied pain-free control subjects (A-B, n=30). STT-mediated function at and below the LOI was significantly impaired in both SCI groups compared with A-B controls (p<0.001), but not significantly different between the two SCI groups (NP vs. no-NP). In contrast, the SCI-NP group had significantly greater impairment of DCML-mediated function at the LOI, as reflected by greater vibratory detection deficits (z=-3.89±0.5), compared with the SCI-noNP group (z=-1.95±0.7, p=0.034). Within the SCI-NP group, NP severity was significantly associated with increased thermal sensitivity below the LOI (r=0.50, p=0.038). Our results suggest that both impaired STT and DCML-mediated function are necessary for the development of NP after SCI. However, within the SCI-NP group, greater NP severity was associated with greater sensitivity to thermal stimuli below the LOI. This finding concurs with other studies suggesting that STT damage with some sparing is associated with NP.